2021
DOI: 10.1093/jpp/rgab090
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA HOXA-AS2 accelerates cervical cancer by the miR-509-3p/BTN3A1 axis

Abstract: Objectives Cervical cancer is an aggressive malignant tumour and causes high mortality in women. LncRNA HOXA-AS2 is a tumour promoter in many cancers. The current work was designed to elucidate the functions of HOXA-AS2 in cervical cancer and the underlying regulatory mechanism. Methods qRT-PCR was conducted to reveal RNA levels. A FISH assay was conducted for the identification of the subcellular location of HOXA-AS2. MTT, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…A total of 18 articles including 1181 patients were included, and the cancer types included gastric cancer ( 24 ), colorectal cancer (CRC) ( 29 , 40 ), hepatocellular carcinoma(HCC) ( 26 , 27 , 41 ), breast cancer ( 18 ), non-small cell lung cancer (NSCLC) ( 19 , 22 ), prostate cancer ( 31 ), osteosarcoma ( 36 , 37 ), bladder cancer ( 30 ), oral squamous cell carcinoma (OSCC) ( 13 ), papillary thyroid cancer (PTC) ( 15 , 16 ), cervical cancer ( 35 ) and glioma ( 47 ). The publication years were from 2015 to 2021, and all patients were from China.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 18 articles including 1181 patients were included, and the cancer types included gastric cancer ( 24 ), colorectal cancer (CRC) ( 29 , 40 ), hepatocellular carcinoma(HCC) ( 26 , 27 , 41 ), breast cancer ( 18 ), non-small cell lung cancer (NSCLC) ( 19 , 22 ), prostate cancer ( 31 ), osteosarcoma ( 36 , 37 ), bladder cancer ( 30 ), oral squamous cell carcinoma (OSCC) ( 13 ), papillary thyroid cancer (PTC) ( 15 , 16 ), cervical cancer ( 35 ) and glioma ( 47 ). The publication years were from 2015 to 2021, and all patients were from China.…”
Section: Resultsmentioning
confidence: 99%
“…HOXA-AS2 was found to be highly expressed in promyelocytic leukemia for the first time ( 55 ) and has been confirmed to be dysregulated in diverse tumor cells, such as osteosarcoma ( 37 ), glioma ( 56 ), NSCLC ( 20 ), CRC ( 57 ), and cervical cancer ( 35 ). It has also been proven to be involved in the biological behavior of many tumor cells as a high-risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies found that HOXA-AS2 was up-regulated in certain cancers. The increased expression of HOXA-AS2 typically predicts poor prognosis for patients with several cancers including cervical cancer (CC) ( Chen and He, 2021 ), oral squamous cell carcinoma (OSCC) ( Chen et al, 2021 ), lung cancer (LC) ( Li and Jiang, 2017 ; Cui et al, 2019 ; Liu et al, 2019 ), colorectal cancer (CRC) ( Li et al, 2016 ; Ding et al, 2017 ), breast cancer (BC) ( Fang et al, 2017 ), thyroid cancer (TC) ( Xia et al, 2018 ; Jiang et al, 2019 ), hepatocellular carcinoma (HCC) ( Wang et al, 2016 ; Zhang et al, 2018 ; Lu et al, 2020 ), acute myeloid leukemia (AML) ( Qu et al, 2020 ), bladder cancer ( Wang F. et al, 2019 ), osteosarcoma (OSA) ( Wang et al, 2018 ; Wang L. et al, 2019 ), lower-grade glioma (LGG) ( Wu et al, 2019 ), prostate cancer (PCa) ( Xiao and Song, 2020 ), gastric cancer (GC) ( Xie et al, 2015 ). A high level of HOXA-AS2 expression is associated with poor overall survival (OS) and clinicopathological characteristics such as differentiation, tumor node metastasis (TNM) stage, lymph node metastasis (LNM).…”
Section: Introductionmentioning
confidence: 99%